Implementasi Pelaksanaan Kegiatan P5 dalam Kurikulum Merdeka dari Pembelajaran Progresif Siswa SMP - Rodiyatun Nufus (Proceedings Series of Educational Studies, 2023)
Abstract: This study aims to find out the implementation of P5 activities as a Pancasila strengthening project in a school, especially junior high schools and equivalent, with the independent curriculum it is certainly a new challenge for educators as well as students because, with the new curriculum students will find it a little difficult to adapt so that with In this research we hope we can understand how students' learning needs both in terms of subject matter as well as interests and talents and find out learning difficulties with the P5 concept. The data collection technique used is a quantitative method where this research is carried out with a direct or experimental approach to students so that it can be explained descriptively. The Strengthening Pancasila Student Profile Project (P5) is a project-based co-curricular activity designed to strengthen efforts to achieve competence and character in accordance with the Pancasila student profile which is prepared based on Graduate Competency Standards, so that the government hopes that every participant who graduates at the school level already has his own abilities and can continue the profile of students in the next level. In the independent curriculum, the profile of Pancasila needs to be increased so that students do not overlook Pancasila values as well in order to create students who have character and can compete both nationally and internationally.Keywords: Independent curriculum, pancasila student profile, p5, implementation of independent learning curriculumAbstrak Penelitian ini bertujuan untuk mengetahui pelaksanaan kegiatan P5 sebagai projek penguatan pancasila di suatu sekolah khususnya SMP dan sederajat, dengan adanya kurikulum merdeka tentu sebagai tantangan baru bagi pendidik juga peserta didik oleh sebab, dengan adanya kurikulum baru peserta didik akan merasa sedikit kesulitas untuk beradaptasi sehingga dengan penelitian ini kami berharap kami dapat memahami bagaimana kebutuhan belajar siswa baik dari segi pokok juga minat dan bakat serta mengetahui kesulitan belajar dengan konsep P5. Teknik pengumpulan data yang di gunakan ialah metode kuantitatif di mana penelitian ini di lakukan dengan pendekatan secara langsung atau eksperimen terhadap siswa sehingga dapat di jelaskan secara deskriptif. Projek Penguatan Profil Pelajar Pancasila (P5) merupakan kegiatan kokurikuler berbasis projek yang dirancang untuk menguatkan upaya pencapaian kompetensi dan karakter sesuai dengan profil pelajar Pancasila yag disusun berdasarkan Standar Kompetensi Lulusan, sehinggga pemerintah berharap bahwa setiap peseta yang lulus dalam jenjang sekolah sudah memiliki kemampuan sendiri dan dapat meneruskan profil pelajar dalam jenjang selanjutnya. Dalam kurikulum merdeka profil pancasila perlu di tingkatkan guna pelajar tidak melipakan nilai nilai pancasila jua guna menciptakan peserta didik yang berkarakter dan dapat bersaing baik di nasional juga internasional.Kata kunci: Kurikulum merdeka, profil pelajar pancasila, P5, implementasi kurikulum merdeka belajar